The case for open source in information and network technology education: experiences from the EuropeAid @lis technology net project. (13th April 2007) - Willmott, Steven; Padget, Julian; Poggi, Agostino; Diaz De Leon, Juan Luis; Casasola, Edgar; Latorre, Homero; Rey, Maria
Open source, open formats and open content have a significant role to play in the development of educational programs. Until now the debate has focused on open methods for delivery and licensing of educational material. But open methods are just as important for education itself, and IT in particular, as they are for delivery. We reflect on the experiences of the @LIS-TechNET project and argue that in emerging regions such as Latin America, a focus on open methods in IT education provides a more sustainable long-term benefit to the IT sector and the economy as a whole than proprietary methods.